2003
DOI: 10.1108/00070700310477059
|View full text |Cite
|
Sign up to set email alerts
|

Croatian food industry – brand equity in selected product categories

Abstract: The purpose of the paper is to determine the level of brand equity in the food industry in the Republic of Croatia, so according to this aim, research on five product categories from the food industry (coffee, chocolate, beer, milk, and carbonated soft drinks) has been conducted. Brand equity is most often defined as an added value that brands add to the products. There are two different approaches to brand equity – financial and customer‐based. With regard to used dimensions of consumer behavior, customer‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Perhaps as a consequence of these developments, we have seen more and more research on branding in grocery and food contexts. Most of this work has focused on how consumers evaluate brands -for example, how brand preference is formed by brand-packaging, price and taste cues (Me ´ndez et al, 2011), how brand positions are perceived (Lee and Liao, 2009), how brands influence quality perceptions (Vranes ˇevic ´and Stancec, 2003) as well as taste judgements (Cerjak et al, 2010), and how customer-based brand equity for food products can be measured (Rajh et al, 2003). In addition, studies have identified which specific image elements are perceived by consumers and make a strong food brand Tikkanen and Va ¨a ¨riskoski, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps as a consequence of these developments, we have seen more and more research on branding in grocery and food contexts. Most of this work has focused on how consumers evaluate brands -for example, how brand preference is formed by brand-packaging, price and taste cues (Me ´ndez et al, 2011), how brand positions are perceived (Lee and Liao, 2009), how brands influence quality perceptions (Vranes ˇevic ´and Stancec, 2003) as well as taste judgements (Cerjak et al, 2010), and how customer-based brand equity for food products can be measured (Rajh et al, 2003). In addition, studies have identified which specific image elements are perceived by consumers and make a strong food brand Tikkanen and Va ¨a ¨riskoski, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Research in the field of food brands focused on how consumers evaluate existing brands-e.g., how customer-based brand equity of food products can be measured [13], how brands influence the perception of the product quality [14] and how packaging, price and taste are involved in forming a brand preference [15]. Moreover, some studies identified the influence of objective or perceived product quality on the price premium, where a brand can obtain a differentiated position motivating consumers to pay more [12] [16].…”
Section: Relevance Of Food Brandsmentioning
confidence: 99%
“…In fact, the brand equity is more capable to impact on marketing actions of its target customers, better than competitors (Aaker 1992;Keller 1993). Even though, the customer based brand equity is important across various industries namely, fast food, retail and airline industries (Kim & Kim 2004: Hartman & Spiro 2005Uslua, Durmus & Kolivar 2013), it is particularly vital to the carbonated soft drink industry (Rajh, Vranesevic & Tolic 2003;Waris 2013;Huang & Liu 2014). Therefore, there is the need to assess the level of youth educated consumers' perceived evaluation on brand equity in the carbonated soft drink industry in Sri Lanka, since extant published studies do not answer the question three, and this is unfilled third gap.…”
Section: Problem Justificationmentioning
confidence: 99%
“…there are many customer based brand equity related studies are conducted in various industries such as in fast food industry (e.g., Kim & Kim 2004), retail industry (e.g., 1-Iartman & Spiro 2005) and airline industry (e.g., Uslua et al 2013), there are few customer based brand equity related studies are conducted in the carbonated soft drink industry. Further, since, customer based brand equity is important to the carbonated soft drink industry (e.g., Rajh et al 2003), there is a need to assess the degree of customer based brand equity in this industry. In addition, Elephant House, Coca Cola and Pepsi…”
Section: Source: Author's Own Systemizationmentioning
confidence: 99%
See 1 more Smart Citation